EMC-compatible shielding magnetic materials for shielding - practical examples - device design - Gräbner, Frank (Wiesbaden Springer, 2021)
The 3rd edition was extended by the chapter "Novel Future Ferrites - Hexagonal Ferrites". The reader is thus given the basics of the various shielding effects in a compressed form. This book is addressed to engineers, scientists, students, researchers and specialists from the practice. Shielding for ensuring EMC in high-frequency and radar technology has been developing with ever increasing dynamics since about 1960. The understanding of the interaction of a magnetic material and the resulting phenomenon of shielding is illustrated by simple examples and practical applications. This book is a translation of the original German 3rd edition EMV-gerechte Schirmung by Frank Gräbner, published by Springer Fachmedien Wiesbaden GmbH, part of Springer Nature 2016. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation. Springer Nature works continuously to further the development of tools for the production of books and on the related technologies to support the authors. The contents - EMC legislation, standardization - Fundamentals of magnetic materials for EMC - Volume Materials - Nanomaterials - Practical examples of shielding and design tips - Nanoshielding - NF shielding - double screen - Polymer Housings - Metal housing with magnetic materials - PCB Shielding - Coaxial cable shield - Textile screen material - Shielding of a wire braid - Basic problem of today's EMV ferrite - Novel future ferrites The target groups Engineers, natural scientists, students, researchers and specialists in the fields: physics, electrical engineering, information technology, communication technology, HF technology, materials science and chemistry The Author Ass. Prof.(BG) Dr.-Ing. Frank Gräbner is head of the EMC/Environment/Nanotechnology department at IMG Electronic & Power Systems GmbH in Nordhausen and gives lectures on electromagnetic compatibility at the University of Rousse in Bulgaria.
Electronic reproduction
Keywords: Electromagnetic compatibility; Electronic books